1994
DOI: 10.1159/000211294
|View full text |Cite
|
Sign up to set email alerts
|

Development of an in vitro Primary Screen for Skin Depigmentation and Antimelanoma Agents

Abstract: An in vitro cell culture assay was developed to identify inhibitors of melanogenesis and agents which produce cytostatic or cytotoxic effects specifically in melanocytes. A total of 50 compounds related to tyrosine, dihydroxyphenylalanine, and hydroquinone (HQ) were tested in vitro in order to determine their effects upon a murine melanocyte cell line, Mel-Ab, that produces copious amounts of melanin in culture. The agents that demonstrated an inhibition of growth or pigment production by 50% (IC50)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
79
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(79 citation statements)
references
References 7 publications
0
79
0
Order By: Relevance
“…When cells reached 40% of confluence, the medium was changed to DMEM supplemented with either 10% FCS alone or 10% FCS with fluvastatin at concentrations: 0.1 μM; 1 μM; 10 μM. Cell viability was determined in triplicates, using crystal violet assay [10,11]. After incubating B16F10 cells with test substances for up to 72 hours, culture medium was removed and the cells were stained with 0.1% crystal violet in 10% ethanol for 5 min at 37°C and rinsed four times.…”
Section: Cell Viability Assaymentioning
confidence: 99%
“…When cells reached 40% of confluence, the medium was changed to DMEM supplemented with either 10% FCS alone or 10% FCS with fluvastatin at concentrations: 0.1 μM; 1 μM; 10 μM. Cell viability was determined in triplicates, using crystal violet assay [10,11]. After incubating B16F10 cells with test substances for up to 72 hours, culture medium was removed and the cells were stained with 0.1% crystal violet in 10% ethanol for 5 min at 37°C and rinsed four times.…”
Section: Cell Viability Assaymentioning
confidence: 99%
“…Some studies supported this hypothesis"). Recently, advances in research on melanogenesis, cell culture assays and development of antimelanoma agents have identified potential pigmentation-reducing agents [16][17][18]. These studies suggested that depigmentation agents have a specific cytotoxic action on melanocytes except for a few agents which inhibit synthesis of melanine without cytotoxic action16.…”
Section: Case Reportsmentioning
confidence: 99%
“…Recently, the application of naturally occurring products as melanin synthesis inhibitors in cosmetics has attracted much interest. 3 For example, plant polyphenols have been the target of several studies, 4 resulting in repeated reviews of their classification, occurrence, structural aspects, reactivity, biochemistry, and biogenesis. Extensive literature is available on the screening of tyrosinase inhibitors, among phenolics of plant origin, and polyphenols are currently the target of numerous studies.…”
mentioning
confidence: 99%